Constituents of the Fruits of Citrus medica L. var. sarcodactylis and the Effect of 6,7-Dimethoxy-coumarin on Superoxide Anion Formation and Elastase Release - Yu-Yi Chan; Tsong-Long Hwang; Ping-Chung Kuo; Hsin-Yi Hung; Tian-Shung Wu (Molecules, 2017)
Investigation of the chemical constituents from the fruits of Citrus medica L. var. sarcodactylis Swingle has led to the characterization of a new sesquiterpene 1 along with thirty-two known compounds. The structure of 1 was established on the basis of 2D NMR spectroscopic and mass spectrometric analyses, and the known compounds were identified by comparison of their physical and spectroscopic data with those reported in the literature. In addition, most of the isolated compounds were evaluated for the activity assayed by the in vitro inhibition of superoxide anion generation and elastase release by human neutrophils. The results showed that only 6,7-dimethoxycoumarin (5) exhibited significant inhibition of superoxide anion generation, with IC50 value of 3.8 ± 1.4 μM.